Dual thermal/electrical-driven compressive recovery behaviors of 3D braided shape memory composite tubes. (1st March 2023) - Qi, Yingying; Xue, Yousong; Gu, Bohong; Sun, Baozhong; Zhang, Wei
Abstract: 3D braided shape memory composite (SMPC) tubes have great potential in designing smart structural components because of high inertia moment and near-net shape manufacturing. Here we developed a 3D braided carbon fiber reinforced shape memory polyurethane-based composite tube and investigated their thermal/electrical shape memory behaviors subjected to compression. The radial and axial compressive behaviors, thermally-electrically shape memory behaviors, and shape recovery forces of the SMPC tubes with different braiding angles were analyzed. The out-of-plane displacement and temperature field were obtained with 3D digital image correlation (DIC) and infrared thermography to characterize transverse compression deformation. We found that the 60° sample had the highest recovery force compared to the other braided angle samples, while the shape recovery speed was lower than small-angle samples. In the transverse compressive electro-thermal recovery test, the 30° sample reaches to glass transition temperature faster at the same voltage, and the 45° sample exhibits maximum shape recovery speed. The 3D braided SMPC tubes exhibited excellent electro-thermal shape memory behaviors and high recovery force, which were expected to extend the application of smart actuators. Graphical abstract: Image 1 Highlights: 3D braided SMPC tubes with thermal-electrical stimuli recovery was prepared. Influence of braiding angle on thermal/electrical shape recovery was presented. Out-of-plane displacement and temperature fields in shape recovery were measured.